THE EFFECT OF UTILIZING MAT-BASED LEARNING RESOURCES ON LEARNING OUTCOMES AND STUDENTS' RESPONSIBILITY ATTITUDES - Ardiana, Erik (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
In the era of digitalization of learning with ICT-based learning resources, it is expected to be able to increase students' attractiveness to be more focused and happily follow the entire learning process. This study aims to determine the effect of the use of ICT-based learning resources on student learning outcomes. This study uses an experimental research method. The research sample selected two classes, namely the experimental class which was given learning treatment with media utilizing ICT-based learning resources and the control class without being given treatment utilizing ICT-based learning resources. Data collection was carried out using an instrument in the form of a multiple-choice test given before learning/pretest and after learning/posttest. The data collection technique used a Questionnaire. Based on the results of the study, it can be concluded that the use of ICT-based learning resources has an effect on student learning outcomes.